Differential coronary resistance microvessel remodeling between type 1 and type 2 diabetic mice: Impact of exercise training - Trask, Aaron J.; Delbin, Maria A. [UNESP]; Katz, Paige S.; Zanesco, Angelina [UNESP]; Lucchesi, Pamela A. (Elsevier B.V., 2012)
The goals of the present study were to compare coronary resistance microvessel (CRM) remodeling between type 1 diabetes mellitus (T1DM) and type 2 diabetes mellitus (T2DM) mice, and to determine the impact of aerobic exercise training on CRM remodeling in diabetes. Eight week old male mice were divided into T1DM: control sedentary (Control-SD), T1DM sedentary (T1DM-SD) induced by streptozotocin, and T1DM exercise trained (T1DM-TR); T2DM: control sedentary (Db/db-SD), T2DM sedentary (db/db-SD), and T2DM trained (db/db-TR). Aerobic exercise training (TR) was performed on a mouse treadmill for 8 weeks. CRMs were isolated and mounted on a pressure myograph to measure and record vascular remodeling and mechanics. CRM diameters, wall thickness, stress-strain, incremental modulus remained unchanged in 11 DM-SD mice compared to control, and exercise training showed no effect. In contrast, CRMs isolated from db/db-SD mice exhibited decreased luminal diameter with thicker microvascular walls, which significantly increased the wall:lumen ratio (Db/db-SD: 5.8 +/- 0.3 vs. db/db-SD: 8.9 +/- 0.7, p<0.001). Compared to db/db-SD mice, coronary arterioles isolated from db/db-TR mice had similar internal diameter and wall thickness, while wall:lumen ratio (6.8 +/- 0.2, p<0.05) and growth index (db/db-SD: 16.2 vs. db/db-TR: 4.3, % over Db/db) were reduced. These data show that CRMs undergo adverse inward hypertrophic remodeling only in T2DM, but not T1DM, and that aerobic exercise training can partially mitigate this process. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Coronary remodeling; Exercise; Vascular; Type 2 diabetes; Type 1 diabetes; Myocardial infarction